Improving The Activity of Stomatological Orthopedic Departments of Modern Technologies on the Basis of SZIT-Analysis (The Peerian Journal, 2023)
Undoubtedly, it is impossible to develop recommendations for improving the activity of one of the structural divisions of the medical dental organization, in this regard, the SZIT analysis of the entire activity of the Medical Dental Organization (MSO) was conducted. An important role is played in the effective development of medical MCM by determining the factors affecting the organizational aspects of activity, the quality of services, financial components and mutual relations with counterparties. The influence of counterparties on the structure and activity of the MSO is carried out at the macro and microeconomic level.